TURNING HILIC/RP POINT - BIOMIMETIC RETENTION PARAMETER - Obradović, Darija; Agbaba, Danica; Lazović, Saša (Archives of Pharmacy, 2023)
The retention profile of imidazoline and serotonin receptor ligands was investigated in dual hydrophilic (HILIC) and reversed-phase (RP) interaction mode (1). The biomimetic meaning of the turining point that defines the switch between the leading retention mechanisms was discussed. The retention profile of 43 imidazoline and serotonin receptor ligands was investigated on an Acclaim Mixed-Mode HILIC-1 column. A mixture of acetonitrile and 20 mM ammonium acetate (pH 6) was used as the mobile phase. The retention was defined as the change of the parameter logk in relation to the volume fraction of acetonitrile in the mobile phase (φ) using the multimodal equation (2). The turning point of the HILIC/RP region was calculated as the minimum value of the multimodal equation. The obtained values of the turning point correlate with the lipophilic profile of the tested compounds (r > 0.70), as well as with the binding potential for total plasma proteins (r > 0.77), and the percentage of drug absorption from the gastrointestinal tract (r > 0.56). The physico-chemical interactions that affect the binding of the tested compounds to arylhydrocarbon receptors (NR.AhR) in the organism, involved in the regulation of toxicological potential, also affect the turning point values (r > 0.60). It can be concluded that the turning point of dual HILIC/RP interactions can be successfully applied in the preliminary characterization of the biopharmaceutical and pharmacokinetic profile of imidazoline and serotonin receptor ligands.